2020
DOI: 10.1039/d0cy00420k
|View full text |Cite
|
Sign up to set email alerts
|

Impact of edge structures on interfacial interactions and efficient visible-light photocatalytic activity of metal–semiconductor hybrid 2D materials

Abstract: The present work systematically investigates the structural, electronic, and optical properties of a MoS 2 / Si 2 BN heterostructure based on first-principles calculations. Firstly, the charge transport and optoelectronic properties of MoS 2 and Si 2 BN heterostructures are computed in detail. We observed that the positions of the valence and conduction band edges of MoS 2 and Si 2 BN change with the Fermi level and form a Schottky contact heterostructure with superior optical absorption spectra. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 66 publications
3
20
0
Order By: Relevance
“…Additional detailed information of the computational methods can be found in our most recent works. 44,59,60 3. RESULTS AND DISCUSSION 3.1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional detailed information of the computational methods can be found in our most recent works. 44,59,60 3. RESULTS AND DISCUSSION 3.1.…”
Section: Methodsmentioning
confidence: 99%
“…To recheck the thermal stability of the pristine monolayer before and after the adsorption of S 8 /Li 2 S x polysulfides, ab initio molecular dynamics (AIMD) simulations were conducted as part of the NVT ensemble using VASP package , by keeping the temperature fixed at 300 K for a timescale of 10 ps and MD-step of 2 fs. Additional detailed information of the computational methods can be found in our most recent works. ,, …”
Section: Methodsmentioning
confidence: 99%
“…It is reported that the pristine graphene have exceptional electron mobility which is chemically active at the edges while not at the surface and which cannot provide a stable potential output, but transition metal oxides (TMO) and transition metal dichalcogenides (TMDs) are inherently inferior in terms of electrical conductivity. It was seen that the most of the TMO, TMDs and other semiconducting 2d nanomaterials hybridized with conductive nanomaterials such as graphene then overall hybrid nanomaterials significantly enhanced the electrical conductivity [153][154][155][156][157][158][159] and contributing to suppressing the interior resistance which is very beneficial for electrochemical reaction rate. In the present section, we mainly focus on the hybrid nanomaterials (i. e. interfacial interaction of 2D/2D, 2D/1D and 2D/0D nanomaterials) to see the electrochemical performance of metal-ions batteries.…”
Section: Interlayer Defects For Mibsmentioning
confidence: 99%
“…edges have been found to strongly influence the structure, electronic properties, magnetism and catalytic activity of many classical 2D materials and their heterostructures, including those of graphene [35][36][37] and MoS 2 . 35,38,39 Therefore, an atomistic understanding of layer-edge interactions in molecularly thin HRPPs is critical for the development of high-performance perovskites required for light detection 16,17 and molecular sensing 40 applications.…”
Section: Introductionmentioning
confidence: 99%